2004
DOI: 10.1007/s00467-004-1474-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of posterior urethral valves and the role of antenatal detection

Abstract: The aim of the study was to investigate the significance of different prognostic factors and long-term renal outcome in boys with posterior urethral valves (PUVs) detected either antenatally or during infancy. A total of 46 cases of PUVs, 23 antenatal and 23 postnatal, were followed prospectively from 1983 to 2003. The mean follow-up time was 12.5 years. The impact of vesicoureteral reflux (VUR), urinary tract infections (UTIs), urinary continence, and renal parenchymal damage on patient outcome was evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 32 publications
5
39
3
Order By: Relevance
“…However, recent registry data from Finland 68 have presented outcomes in babies with PUVs (n = 46), with 23 diagnosed prenatally (with no intervention) and 23 diagnosed postnatally (with apparently 'normal' ultrasound appearances in the majority). This cohort study is unique, in that long-term follow-up over 10 years was performed (mean 12.5 years, range 5.5-20.1 years).…”
Section: Systematic Review Of the Accuracy Of Antenatal Diagnosis Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent registry data from Finland 68 have presented outcomes in babies with PUVs (n = 46), with 23 diagnosed prenatally (with no intervention) and 23 diagnosed postnatally (with apparently 'normal' ultrasound appearances in the majority). This cohort study is unique, in that long-term follow-up over 10 years was performed (mean 12.5 years, range 5.5-20.1 years).…”
Section: Systematic Review Of the Accuracy Of Antenatal Diagnosis Andmentioning
confidence: 99%
“…Some researchers who have studied these patients prospectively have reported significant renal morbidity (notably end-stage renal failure requiring dialysis or transplantation) 68 and others have found acceptable quality-of-life scores in a majority in the long term. 83 Such data, which will be useful in understanding the overall cost-effectiveness of VAS, are not currently available from the PLUTO trial and hence were not included in this analysis.…”
Section: Strengths and Limitations In Relation To Other Studiesmentioning
confidence: 99%
“…The authors of the latter study note that for the more severely affected patients, the functional outcome may be primarily determined by the severity of intrauterine obstruction and presence of renal dysplasia and not significantly altered by early diagnosis and treatment; however, for patients with more moderate disease, long-term prognosis may be improved by prenatal diagnosis and early interventions (Kousidis, et al, 2008). Other studies have not shown a statistically significant difference in outcomes between patients with renal dysplasia and those with normal-appearing kidneys (Nickavar, et al, 2008;Ylinen et al, 2004).…”
Section: Natural History Of Lower Urinary Tract Obstructionmentioning
confidence: 94%
“…Obstructive uropathy, renal hypoplasia, and dysplasia constitute 39% of the cases of end stage kidney disease (ESKD) in childhood in Germany, including the cases of boys with PUV [5]. The incidence of ESKD in children with PUV varies between 13 and 38% [6,7]. Results from previous studies imply a variety of prognostic factors for the development of ESKD, including creatinine concentration, bilateral or persistent vesicoureteral reflux (VUR), delayed diagnosis, poor detrusor function, delayed achievement of urinary continence, oligohydramnios, ventilatory support after birth, and breakthrough urinary tract infections [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%